Natural Semantic Metalanguage as a Pedagogical Bridge in Multilingual Higher Education Classrooms - Nahida Akter Poly (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2026)
This article explores how Natural Semantic Metalanguage (NSM) can function as a pedagogical bridge in multilingual higher education classrooms. In linguistically and culturally diverse classrooms, students and instructors often encounter culture-specific concepts and communicative practices that cannot be fully explained through direct translation or dictionary definitions. Drawing on NSM semantic explications and cultural scripts, this article examines selected Bangla concepts—adda (আড্ডা), maya (মায়া), and shukh (সুখ)—as well as Bangladeshi communicative practices related to respect for elders, family obligation, and indirect communication. The analysis shows that NSM can make culturally embedded meanings more accessible across linguistic and cultural boundaries while preserving their semantic richness. The article argues that NSM has pedagogical value not only for international students and instructors but also for monolingual English-speaking classroom participants who encounter unfamiliar cultural meanings. By offering a simple, cross-translatable framework for explaining complex meanings, NSM can support intercultural understanding, meaning negotiation, and more inclusive teaching and learning practices in multilingual higher education classrooms.